Adaptação transcultural do instrumento Functional Mobility Assessment (FMA), para uso no Brasil - Paulisso, Debora Caires (Universidade Federal de São Carlos, 2016)
Introduction: Functional Mobility Assessment – FMA is a tool developed in United States of America that seeks to assess the satisfaction of users of mobility devices, related to its functionality when using these devices. In Brazil there are few studies investigating the influence of the use of Assistive Technologies and the social participation of individuals and, regarding the use of assistive devices for mobility and satisfaction with the functionality there is only one reference to recently standardized instrument. Thus, surveys show the need for further researches directed to this theme in Brazil. Aim: general purpose in this research was to carry out the cross-cultural adaptation process of the instrument FMA. Method: The cross-cultural adaptation procedure of the instrument was based on two international guidelines. There was formal authorization for use of the instrument and approved by the Ethics Committee for Research (Report nº: 939.039). Results: The first translation was done by two independent translators and later discrepancies between the two translations were resolved and created a single version. The single version has undergone a back translation (Portuguese -English) and was sent and analyzed by the authors of the instrument and then by 11 experts, including occupational therapists, physiotherapists and all translators. Also a personal meeting with the authors of the tool was performed. The pre-test version was administered to 24 participants, who were also interviewed on the understanding of each phrase of the instrument and obtained nearly 100% understanding of sentences. The last stage consisted reports analysis by the authors of the original instrument to approve the final version. Conclusion: the cross-cultural adaptation was concluded and the instrument is ready to undergo further studies to obtain psychometric measures in the Brazilian population.
Keywords: Adaptação Transcultural; Tecnologia Assistiva; Mobilidade Funcional; Satisfação Pessoal; Funcionalidade; Terapia Ocupacional; Cross cultural adaptation; Assistive Technology; Functional Mobility; Personal Satisfaction; Functionality; Occupational Therapy; CIENCIAS BIOLOGICAS